2012
DOI: 10.1590/s0006-87052012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium sulphate on maize crops under no tillage

Abstract: The objectives of this work were to evaluate the management of N and S (as ammonium sulphate) fertilization under notillage system on the components of maize productivity and on N and S accumulation in the crop, as well as to evaluate the minimum value of the Nitrogen Sufficiency Index (NSI 0.95) as an indicator for side dressing requirements. The experiment had a completely randomized block design with six treatments and four replications carried out in Red Latosol dystrophic soil (Hapludox), in Campo Mourão,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
(22 reference statements)
3
5
1
7
Order By: Relevance
“…This fact elucidates the reason chlorophyll contents is greater in the MS media, which provides more nitrogen and favours higher chlorophyll synthesis. This finding is contrary to the statement of Silva et al (2012) that the chlorophyll concentration is correlated with the concentration of nitrogen in the plant, as well as crop productivity. Based on this principle, the chlorophyll index has been used not only during in vitro culture, but also in the management of fruit already installed in the field, such as citrus and pecan (HARDIN et al, 2012;SOUZA et al, 2011).…”
Section: Nutrient Mediumcontrasting
confidence: 99%
“…This fact elucidates the reason chlorophyll contents is greater in the MS media, which provides more nitrogen and favours higher chlorophyll synthesis. This finding is contrary to the statement of Silva et al (2012) that the chlorophyll concentration is correlated with the concentration of nitrogen in the plant, as well as crop productivity. Based on this principle, the chlorophyll index has been used not only during in vitro culture, but also in the management of fruit already installed in the field, such as citrus and pecan (HARDIN et al, 2012;SOUZA et al, 2011).…”
Section: Nutrient Mediumcontrasting
confidence: 99%
“…All maize varieties were given higher N accumulation at full recommended nitrogen fertilizer application as compared to half recommended nitrogen application and without fertilizer N application. da Silva et al [48] found that grain N accumulation was higher in all treatments with ammonium sulphate fertilization. The N accumulation in plants and grains was in agreement with the reports by Zotarelli et al [50].…”
Section: Shoot and Grain N Accumulation And N Harvest Index Ofmentioning
confidence: 91%
“…Similarly, Anbessa and Juskiw [7] found that biomass N yield was increased with the rate of N fertilizer. The correlation coefficients between maize productivity and N accumulated in shoots (leaves, corncobs, straws, and stems) were high [48]. Moser [46] found that maize varieties differed significantly in shoot N concentration and shoot N accumulation and shoot N concentration was increased with increased rate of nitrogen.…”
Section: Shoot and Grain N Accumulation And N Harvest Index Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…As leituras instantâneas de maneira não destrutiva de folhas, proporcionadas pelo clorofilômetro, apresentam-se como alternativa de indicação do teor de clorofila presente na folha da planta (KLOOSTER et al, 2012). O teor de clorofila correlaciona-se com a concentração de N na planta e, também, com a produtividade das culturas (SILVA et al,2012b). Em algumas frutíferas, como citros (SOUZA et al, 2011) e nogueira-pecã (HARDIN et al, 2012), o uso do índice SPAD tem-se mostrado adequado para auxiliar no manejo na adubação nitrogenada.…”
Section: Content Of Chlorophyll and Spad Index In Pineapple CV Vitórunclassified